THE EFFECT OF SERVICE QUALITY INTEGRATION AND TIMELINESS ON CUSTOMER SATISFACTION AT DAMAR KEBAYA TAILORS IN PERUMNAS WAY KANDIS BANDAR LAMPUNG - Dery Dwi Hartanto; Dora Rinova (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes how service quality and order processing speed impact customer satisfaction at Damar Kebaya Tailor. A quantitative research approach was employed, with data collection conducted through structured questionnaires distributed to the company's customers. The collected data were then analyzed using multiple linear regression, encompassing both partial hypothesis testing (t-tests) and simultaneous testing (F-tests) using SPSS. The results of the single tests demonstrated that each variable service quality and order processing speed had an independent and statistically significant positive effect on customer satisfaction. Furthermore, the simultaneous test revealed that both variables, when analyzed together, had a significant combined influence on customer satisfaction. These findings indicate that improving service quality and ensuring timely order delivery constitute viable strategies for enhancing overall customer satisfaction at Damar Kebaya Tailor.